RANCANG BANGUN SISTEM INFORMASI GEOGRAFIS PEMETAAN HUTAN PADA KABUPATEN LABUHAN-BATU - Ibnu Rasyid Munthe; Eliyas Wiko Wardana; Gomal Juni Yanris (LPPM Universitas Abdurrab, 2021)
The agricultural, plantation and forestry industries, which are the main choices of the population to meet household food needs and boost the community's economy, are very much in accordance with the geographical contours of Labuhanbatu Regency. A geographic information system that can provide position information, location coordinates, forest areas, forest information in Labuhanbatu Regency, and search paths for forest area locations. A web-based Geographical Information System (GIS) is required to determine the current position and location of forests. The waterfall method is used to build this GIS framework, which involves stages such as analysis, design, code generation, testing, and maintenance. MySQL is a database management system. PHP, Javascript, and HTML are used to create programming languages. Bootstrap user interface implementation. Black box testing is used to verify software. The test results show that the GIS meets the requirements and can solve system problems.